INCIDENTALLY FOUND METASTATIC PROSTATIC CARCINOMA IN A THERAPEUTIC ORCHIECTOMY SPECIMEN - Bilal, Muhammad; Uddin, Zeeshan; Ayaz Khan, Mohammad (Journal of Ayub Medical College Abbottabad, 2018)
ABSTRACT: Metastatic tumor involving the testis is a rare event. Incidental discovery of metastatic cancer in a therapeutic orchiectomy is even rarer. We report a case of metastatic adenocarcinoma prostate found incidentally in one of the bilateral therapeutic orchiectomy specimen. The patient was a 55 year-old man presenting with back ache and generalized body aches. Clinical examination showed malignant feel of prostate. Bone scan revealed metastatic disease and a serum PSA level of >100 ng/ml. Clinical diagnosis of carcinoma prostate was established and subsequent bilateral orchiectomy for hormonal deprivation was performed. On gross examination of left testis, there was a small 0.7 X 0.6 cm suspicious area. Microscopically, this area showed an infiltrating tumor in the interstitium with entrapped seminiferous tubules. Focal intravascular tumor deposit was also noted. Immunohistochemical stain for prostate-specific antigen was positive in the tumor, which confirmed the diagnosis of metastatic prostate adenocarcinoma. KEY WORDS: metastasis, microscopy, orchiectomy, prostate cancer, testis. Metastatic tumour involving the testis is a rare event. Incidental discovery of metastatic cancer in a therapeutic orchiectomy is even rarer. We report a case of metastatic adenocarcinoma prostate found incidentally in one of the bilateral therapeutic orchiectomy specimens. The patient was a 55-year-old man presenting with back ache and generalized body aches. Clinical examination showed malignant feel of prostate. Bone scan revealed metastatic disease and a serum PSA level of >100 ng/ml. Clinical diagnosis of carcinoma prostate was established and subsequent bilateral orchiectomy for hormonal deprivation was performed. On gross examination of left testis, there was a small 0.7 X 0.6 cm suspicious area. Microscopically, this area showed an infiltrating tumour in the interstitium with entrapped seminiferous tubules. Focal intravascular tumour deposit was also noted. Immunohistochemical stain for prostate-specific antigen was positive in the tumour, which confirmed the diagnosis of metastatic prostate adenocarcinoma. Keywords: Metastasis; Microscopy; Orchiectomy; Prostate Cancer; Testis